The Impact of Work Ability, Work Discipline and Work Motivation on the Work Performance of Employees of the Office of the National Unity and Political Agency of North Sumatra Province - Nizamuddin; Wilchan Robain (Yayasan Multidimensi Kreatif, 2024)
The study aims to determine whether work ability, work discipline and work motivation partially and simultaneously have a positive and significant impact on employee work performance at the Office of the National Unity and Politics Agency of North Sumatra Province. The sample was 54 respondents, The results of the study showed that ability had a positive and significant impact on employee work performance at the Office of the National Unity and Politics Agency of North Sumatra Province. Tested and acceptable based on the t-value of the work ability variable (X1) is 2.274 and the t-table value is 2.008, then t-count> t-table (2.274> 2.008) and the Sig. value <0.05 The magnitude of the impact of ability (X1) on work performance (Y) is 0.025, Discipline has a positive and significant impact on employee work performance at the Office of the National Unity and Politics Agency of North Sumatra Province. Tested and acceptable based on the t-value of the discipline variable (X2) is 8.527 and the t-table value is 2.008, then t-count> t-table (8.527> 2.008) and the Sig. value <0.05 The magnitude of the impact of discipline (X2) on work performance (Y) is 0.686, Work motivation has a positive and significant effect on employee work performance at the Office of the National Unity and Politics Agency of North Sumatra Province. Tested and acceptable based on the t-value of the work motivation variable (X3) is 2.939 and the t-table value is 2.008, then t-count> t-table (2.939> 2.008) and the Sig. value <0.05. The magnitude of the impact of work motivation (X3) on work performance (Y) is 0.211 Ability, discipline and work motivation simultaneously have a positive and significant impact on employee work performance at the Office of the National Unity and Politics Agency of North Sumatra Province. Tested and acceptable based on the F count value of 75.124 with a significance level of 0.000, greater than the F table value with a significance level of 95% (α = 0.05).